Lemony Snicket's A series of unfortunate events - Silberling, Bradley; Carrey, Jim, 1962-; Aiken, Liam.; Browning, Emily, 1988-; Spall, Timothy, 1957-; O'Hara, Catherine; Law, Jude, 1972-; Lubezki, Emmanuel; Newman, Thomas; Snicket, Lemony; Snicket, Lemony; Snicket, Lemony; et al. (Hollywood, Calif. : Paramount Home Entertainment, 2005)
Violet, Klaus, and Sunny Baudelaire are taken in by a series of oddball relatives and others after their wealthy parents are killed in a fire. The first to take them in is the dastardly and cunning Count Olaf, who is only interested in their inheritance.
Originally released as a motion picture in 2004.
Based on the books "The bad beginning", "The reptile room" and "The wide window" by Lemony Snicket.
Special features: Commentary by Brad Silberling; Brad Silberling and the real Lemony Snicket commentary; bad beginnings; dismal deletions; obnoxious outtakes.
Director of photography, Emmanuel Lubezki ; editor, Michael Kahn ; music, Thomas Newman ; costume designer, Colleen Atwood ; production designer, Rick Heinrichs.
Jim Carrey, Liam Aiken, Emily Browning, Timothy Spall, Catherine O'Hara, Billy Connolly, Cedric the Entertainer, Luis Guzman, Jennifer Coolidge, Jude Law.
MPAA rating: PG; for thematic elements, scary situations and brief language.
Keywords: Orphans -- Drama; Inheritance and succession -- Drama; Films for the hearing impaired; Feature films